The effects of urbanization on the ant fauna of the Swan Coastal Plain near Perth, Western Australia - Majer, Jonathan; Brown, K. (1986)
The ant fauna in 33 Perth gardens was surveyed by hand collecting, and pitfall trapping. The resulting catch was considered at the species level and also four ant variables (abundance, species richness, species diversity and species evenness) were investigated for correlatlon wlth garden botanical and management variables.Forty-seven ant species from 22 genera were recorded from the gardens. Thirty-six species occurred in less than one third of the gardens which were studied. Some of the species were absent or uncommon in adjacent native vegetation indicating that they were favoured by urbanization while other species from the native vegetation were unable to colonize, or persist in, the gardens.Ant species richness and diversity were significantly lower in gardens than native vegetation while species evenness did not statistically differ between the two types of land use. The ant fauna was enhanced by the length of time the garden had been established, and also increased garden area, leaf litter and ground cover. Gardens where pesticides were used, where tall shrubs were dense or where management (e.g. watering) was intense, had a depauperate ant fauna.This study has indicated that urban gardens are an important refuge for ants and maybe, because ant species richness often reflects that of other invertebrates groups, for a wide range of other invertebrates.